Concepts of Reusing Wind Turbine Blades in Civil Engineering Constructions - Halicka, Anna; Buda-Ożóg, Lidia; Jabłoński, Łukasz; Jurek, Michał; Jakubiak, Natalia; Jabłoński, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Wind turbines have become an important source of renewable energy in recent years, but recycling them is difficult due to their material properties. The paper indicates the possibility of using turbine blades to produce elements that can be filled with concrete and used as members of small geotechnical structures: retaining walls, point and well foundations, foundations for railings, fences, road signs, etc., as well as excavation linings and shoring walls. In these solutions, concrete-filled elements of turbine blades constitute a form (formwork) for concrete, protecting it against environmental influences, and can also cooperate with concrete in transferring loads.
Keywords: wind turbine blades; recycling; upcycling; geotechnical structures; composite structures